Assessment of Migration Policy Measures Implemented in the Russian Far East - Shmidt, Yury D.; Ivashina, Natalya V. (Economy of Regions, 2021)
The present paper analyses migration policy measures implemented in the Russian Far East, namely, State Programme to Assist the Voluntary Resettlement of Compatriots Living Abroad to the Russian Federation, the Far-Eastern Hectare Programme, establishment of Priority Development Areas (PDAs) and territories with a special regime of economic activity. The synthetic control method was applied to quantitatively assess how the adopted measures affect the migration outflow from regions of the Far Eastern Federal District. According to this method and relevant statistics, constituent entities of the Far Eastern Federal District were compared with control regions of the Siberian Federal District, where these policy tools have not been introduced. Comparable areas had similar socio-economic development trends and migration flows in the period preceding the implementation of the state programmes. To analyse the impact of migration policy changes in 2011-2018, the difference between outflow values of the Far Eastern and synthetic control regions was calculated. The results showed that the average estimated values are negative and significantly different from zero. This indicates a positive effect of new migration mitigation measures on reducing the outflow from the Russian Far East. Future research will separately assess the effectiveness of each migration policy tool implemented in the Far Eastern Federal District.